Membumikan al-Quran di Negeri Seribu Suluk (Studi Lapangan di Islamic Center Rokan Hulu) - Syahrul Rahman (STAIN Bengkalis, 2020)
Maintaining the purity of the koran by memorizing is still needed despite many media originality of the qoran, it could be a compact disc, computer, and others. In addition to the media’s weakness, memorizing the qoran for a muslim is one worship that is judjed with great rewards. The article would like to point out the extent to which a person needs to know the forms of the qoran’s memorization of the method and whether knowing it gives a part in memorizing the qoran. The research is ground based by making the two educational addresses in the Islamic Center; Junior High State Tahfizh Madani and MA Tahfidz sand filling as an object of this research. As for the result of this study, a mas’s success in memorizing koran has nothing to do with his introduction to a single quran methode. However, the greatest role in completing memorization is a great will built on pure will as a form of religious charity. On a large scale, Junior High State Tahfizd and MA Tahfidz studied two great programs, the first is quarantine program held in Monday through Sunday in Islamic Center, this overnight activity is for SD students who wish to memororize the quran. Second, the quran Safari program, visiting high scholl, was carried out on Friday morning.